Impact of HER2 Expression on the Prognosis of Muscle-Invasive Bladder Cancer Patients Treated with Bladder-Preservation Comprehensive Therapy - Yatong Chen; Fei Luo; Tingji Zhang; Jian Li (Biological Procedures Online)
Abstract Background HER2 expression has been confirmed to be associated with bladder cancer aggressiveness. Anti-HER2 RC48-ADC is approved in China for the treatment of patients with advanced urothelial carcinoma with failed chemotherapy who are HER2 positive (IHC 2 + or 3 +). The discovery of HER2 positivity in urothelial carcinoma and the development of anti-HER2 drugs have brought new hope for bladder preservation treatment in MIBC. Objective To investigate HER2 expression in MIBC patients and its correlations with clinical characteristics, to analyze the impact of HER2 expression on the prognosis of MIBC patients administered bladder-preservation comprehensive therapy, and to explore the efficacy and safety of RC48-ADC in MIBC patients administered bladder-preservation comprehensive therapy. Methods We retrospectively collected information on MIBC patients. All 217 patients underwent cTURBT, of whom 175 received GC chemotherapy, while the remaining 42, due to intolerance to GC chemotherapy and HER2 positivity (IHC 2 + or 3 +), received RC48-ADC treatment. Of the 175 patients administered cTURBT combined with GC chemotherapy, 92 and 83 were HER2-negative and HER2-positive, respectively. Recurrence-free survival (RFS) and overall survival (OS) in HER2-negative and HER2-positive patients were compared to analyze the correlation between HER2 expression and prognosis. RFS and OS in the 83 HER2-positive patients administered cTURBT combined with GC chemotherapy and the 42 HER2-positive patients administered cTURBT combined with RC48-ADC were compared to analyze the differences in prognosis between the two treatment methods. The adverse reactions of GC and RC48-ADC were also compared. Results Among the 217 included patients, 125 (57.6%) were HER2 positive (IHC 2 + or 3 +). HER2 positivity was significantly associated with tumor size, multifocality, pathological grade, tumor stage, and pelvic lymph node metastasis (P < 0.05). Totally 175 patients underwent cTURBT combined with GC chemotherapy, including 92 HER2-negative and 83 HER2-positive cases. There were no significant differences in gender, age, smoking status, tumor location, and ECOG score between the two groups (P > 0.05), but the proportions of patients with tumors > 3 cm, multifocal tumors, T3 stage, high-grade tumors, and pelvic lymph node metastasis were higher in the HER2-positive group versus the HER2-negative group (P < 0.05). Tumor recurrence rate in the 83 HER2-positive patients was 67.5%, with a median RFS of 19.0 months (95% CI: 10.3–27.7). Totally 22 deaths occurred during the follow-up period, with a median OS of 56.0 months (95% CI: 45.7–66.3). In the 92 HER2-negative patients, the tumor recurrence rate was 56.5%, with a median RFS of 36.0 months (95% CI: 26.1–45.9); 4 deaths occurred during the follow-up period, with the median OS not reached. After cTURBT, of the 125 HER2-positive patients examined, 83 were included in the GC treatment group versus 42 in the RC48-ADC group. There were no differences in gender, age, smoking status, tumor location, tumor size, multifocality, clinical T stage, pathological grade, pelvic lymph node metastasis, and ECOG score between the two groups (P > 0.05). In the GC group, 56 recurrences (67.5%) were detected during the follow-up period, with a median RFS of 19.0 months (95% CI: 10.3–27.7); meanwhile, 22 deaths (52.4%) occurred, with a median OS of 56.0 months (95% CI: 45.7–66.3). In the RC48-ADC group, 15 recurrences (35.7%) were recorded during the follow-up period, with the median RFS not reached; there were 2 deaths (4.8%), with the median OS not reached. The incidence rates of any-grade and grade ≥ 3 adverse reactions were both lower in the RC48-ADC group than in the GC treatment group. Conclusions This study confirms that cTURBT combined with RC48-ADC treatment for HER2-positive MIBC is superior to combined GC treatment in terms of RFS and OS, representing an effective treatment regimen for bladder preservation in MIBC patients.